Density functional theory studies of the adsorption of Cr (VI) on Fe-(hydr) oxide: Gibbs free energies and pH effect. (June 2019) - Acelas, N Y; Flórez, E
Abstract: Adsorption of chromium (VI) on iron oxides is a potential removal method from industrial wastewater. Cr (VI) is a toxic specie for human health due to its easy mobility in the environment. Currently, US EPA drinking water standards establish a maximum Cr level of 100 μg/L. Since the adsorption process occurs in the solid/liquid interface, pH is one of the main factors that affect this process and it is a very important parameter to study. Understanding the adsorption process and the molecular geometries of complexes, is essential to predict the environmental transport of Cr (VI) and to develop appropriate models for the remediation of Cr (VI). Therefore, in this work, we describe the adsorption of Cr (VI) onto Fe-hydr (oxides) through computational methods. A complete characterization of the adsorbed surface complexes was performed, and three different pH conditions were simulated (acidic, intermediate and basic). It was found that, the thermodynamic favourability of the different adsorbed complexes was directly related to the pH. Bidentate complex (BB) was the most thermodynamically favourable complex with an adsorption energy of -143.3 kJ/mol under acidic pH conditions.